Gambaran Karakteristik Dan Pengetahuan Tentang Stunting Pada Ibu Yang Memiliki Balita Usia 36-60 Bulan Di Klinik Romauli Tahun 2024 - Ritha, Aniah; Viosita Simbolon, Vani; Sinaga, Desriati; Arisandi, Ermawaty; Sinabariba, Melina (Jurnal Maternitas Kebidanan, 2024)
Toddlerhood is the most important period in the life cycle, because at the age of 0 to 5 years toddlers experience physical, mental and behavioral development.Stunting is a condition where a child experiences growth disorders, so that the child's height does not match his age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. Based on a preliminary study in April, it is found that most mothers did not know for sure about stunting in toddlers. Research Objective: To determine the characteristics and knowledge of mothers about stunting in toddlers aged 36-60 months. Research Method: This type of research is descriptive. The sampling technique was probability sampling with purposive techniques. The location of this research is. With 35 respondents. The measuring instrument used is a questionnaire, Research Results: The results show that out of 35 Respondents, there are Respondents in the category of good knowledge 13 respondents (37,14%), the category of sufficient knowledge 9 Respondents (26,5%), and the category of low knowledge 13 respondents (37,14%). Conclusion: Based on the results of the study, it shows that the highest percentage aspect is good and low knowledge.. Health workers are expected to increase counseling in clinics so that mothers' knowledge about stunting in toddlers increases and invite mothers to seek information from health workers.